Rush to judgment. - Deep, Said (Quill)
Focuses on the media and public's assumptions that the April 1995 Oklahoma City bombing had Middle East origins. Criticism against Steven Emerson, producer of the documentary `Jihad in America'; Factors contributing to the anti-Middle East fervor; Improvement of the image of Arab- and Muslim-Americans.